Ticks and tickborne diseases in Global South countries: impact and implications of environmental changes - Shahzad, Sammuel; Akinsulie, Olalekan Chris; Idris, Ibrahim; Devnath, Popy; Ajagbe, Damilare; Aliyu, Victor Ayodele; Oladoye, Moyinoluwa Joshua; Ukauwa, Chizaram; Ugwu, Charles Egede; Ajulo, Samuel; Oyeleye, Blessing Simon; Ikele, Chinelo Geraldine; et al. (Frontiers in Tropical Diseases, 2025)
Ticks and tick-borne diseases (TBDs) are escalating health and veterinary threats in the Global South, driven by environmental change, human activity, and socioeconomic vulnerability. Ticks transmit bacterial, viral, and protozoal pathogens, causing significant public health and economic burdens. Climate shifts and land-use changes have expanded tick habitats, intensifying disease transmission. This review examines the distribution of major tick species in the Global South and explores how ecological disruptions influence disease dynamics. Regional case studies from Africa, the Middle East, and South Asia highlight the impact on human health, livestock productivity, and food security. Addressing this growing threat requires integrated One Health strategies, improved public awareness, enhanced veterinary services, and investment in surveillance and vaccine development. International cooperation and strong policy frameworks are vital to mitigate the spread and impact of TBDs.